Randomized controlled trial of a messaging intervention to increase fruit and vegetable intake in adolescents: Affective versus instrumental messages. Issue 4 (6th October 2016) - Carfora, Valentina; Caso, Daniela; Conner, Mark
Abstract : Objective: The present research aimed to test the efficacy of affective and instrumental text messages compared with a no‐message control as a strategy to increase fruit and vegetable intake (FVI) in adolescents. Design: A randomized controlled trial was used test impact of different text messages compared with no message on FVI over a 2‐week period. Method: A total of 1, 065 adolescents (14–19 years) from a high school of the South of Italy completed the baseline questionnaire and were randomly allocated to one of three conditions: instrumental messages ( N  = 238), affective messages ( N  = 300), and no messages ( N  = 521). Students in the message conditions received one message each day over a 2‐week period. The messages targeted affective (affective benefits) or instrumental (instrumental benefits) information about FVI. Self‐reported FVI at 2 weeks was the key dependent variable. Analyses were based on the N  = 634 who completed all aspects of the study. Results: Findings showed that messages significantly increased FVI, particularly in the affective condition and this effect was partially mediated by changes in affective attitude and intentions towards FVI. Conclusion: Text messages can be used to increase FVI in adolescents. Text messages based on affective benefits are more effective than text messages based on instrumental benefits. Statement of contribution What is already known on this subject? Text messages have been shown to promote positive change in health behaviours. However, the most appropriate target for such text messages is less clear although targeting attitudes may be effective. What does this study add? This randomized controlled study shows that text messages targeting instrumental or affective attitudes produce changes in fruit and vegetable intake (FVI) in adolescents. Text messages targeting affective attitudes are shown to be more effective than text messages targeting instrumental attitudes. The effect of affective text messages on FVI was partially mediated by changes in affective attitudes.